The Old Everett High School: A Catalyst to Revitalize the City. - Fox, Laura.; Jasinski, Laura; Madaro Moro, Adrian; Morson-Matra, Anita. (Tufts University. Tisch Library., 2018)
2012 M.A. in Urban and Environmental Policy and Planning Field Project. Client: City of Everett.